Handbook of Clinical Nutrition and Aging - Bales, Connie W.; Ritchie, Christine S. (Nutrition and Health,, 2009)
As the older adult population continues to grow, so will the prevalence and incidence of age-related disorders. In Handbook of Clinical Nutrition and Aging, Second Edition , the editors and contributors ( a panel of recognized academic nutritionists, geriatricians, clinicians and scientists) have thoroughly updated and revised their widely acclaimed first edition with fresh perspectives and the latest scientific and clinical developments in age-associated disease. New chapters tackle ecological perspectives on adult eating behavior, and behavioral theories applied to nutritional therapies in aging, while topics such as Sarcopenia and Cachexia are discussed in greater detail. The authors outline the physiological basis for each disorder, provide the latest information about the interaction of nutrition with these conditions, and review the potential routes and mechanisms for clinical intervention. Timely and authoritative, Handbook of Clinical Nutrition and Aging, Second Edition is a unique, comprehensive resource and will prove a valuable guide to all nutritionists, physicians, nurses, dietitians, and speech-language and occupational therapists who provide care for the rapidly expanding aging population.